Cerita Pendek Berlatar Pandemi Covid-19 sebagai Bahan Edukasi Karakter Berkebinekaan Global - Sufanti, Main; Purwati, Panca Dewi; Cahyati, Jeni Nur (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2022)
The Covid-19 pandemic has inspired the writing of short stories. Suara Merdeka, and Kompas contain short stories set against the backdrop of the Covid-19 pandemic. These stories have the potential to become educational materials to strengthen the character of global diversity. The aims of this study are (1) to find short stories set in the Covid-19 pandemic in newspapers, (2) to analyze the values in short stories that have the potential to be used as educational materials to strengthen the character of global diversity. This research method is descriptive qualitative. Data in the form of words, sentences, and paragraphs with data sources from short stories set in the Covid-19 pandemic published in Kompas, Solopos, and Suara Merdeka April–September 2020 editions. Data collection uses reading, listening, and note-taking techniques. Theoretical triangulation was used for data validation. Data analysis used heuristic and hermeneutic techniques. The results of this study are as follows. (1) Found 15 short stories set in the Covid-19 pandemic in the April–September 2020 editions of Kompas, Solopos, and Suara Merdeka newspapers. The background of the Covid-19 pandemic in this story can be found through story topics explicitly related to the pandemic, (2 ) Found 7 short stories that contain values supporting characters of global diversity. These values are: maintaining tradition, tolerance for diversity, having multiple points of view in looking at problems, and having a global perspective. These values have the potential to become educational materials that can strengthen the character of global diversity through the appreciation of short stories AbstrakPandemi Covid-19 memberi inspirasi penulisan cerita pendek. Suara Merdeka, dan Kompas memuat cerita pendek yang berlatar pandemi Covid-19. Cerita-cerita ini berpotensi menjadi bahan edukasi untuk memperkuat karakter berkebinekaan global. Tujuan penelitian ini adalah (1) menemukan cerita pendek yang berlatar pandemi Covid-19 di surat kabar, (2) menganalisis nilai-nilai dalam cerita pendek yang berpotensi sebagai bahan edukasi penguat karakter berkebinekaan global. Metode penelitian ini adalah deskriptif kualitatif. Data berupa kata, kalimat, dan paragraf dengan sumber data cerita pendek berlatar pandemi Covid-19 yang dipublikasikan di Kompas, Solopos, dan Suara Merdeka edisi April–September 2020. Pengumpulan data menggunakan teknik baca, simak, dan catat. Triangulasi teori digunakan untuk validasi data. Analisis data menggunakan teknik heuristik dan hermeneutik. Hasil penelitian ini sebagai berikut.  (1) Ditemukan 15 cerita pendek yang berlatar pandemi Covid-19 di surat kabar Kompas, Solopos, dan Suara Merdeka edisi April–September 2020. Latar pandemi Covid-19 dalam cerita ini dapat ditemukan melalui topik cerita secara eksplisit terkait dengan pandemi, (2) Ditemukan 7 cerita pendek yang mengandung nilai-nilai pendukung karakter berkebinekaan global. Nilai-nilai tersebut adalah: memelihara tradisi, toleransi terhadap keanekaragaman, memiliki banyak sudut pandang dalam melihat masalah, dan berwawasan mendunia.  Nilai-nilai ini berpotensi menjadi bahan edukasi yang dapat memperkuat karakter kebinekaan global melalui apresiasi cerita pendek.